B11 Vocalisation as a viable assessment for minipigs transgenic for the huntington gene?. (September 2018) - Rieke, Lorena; Schubert, Robin; Matheis, Tamara; Muratori, Lisa; Freisfeld, Frauke; Motlik, Jan; Fels, Michaela; Kemper, Nicole; Schuldenzucker, Verena; Reilmann, Ralf
Abstract : Backround: Large animal models, such as the transgenic (tg) Huntington disease (HD) minipig, have been proposed to improve translational reliability and assessment of safety, efficacy and tolerability in preclinical studies. Minipigs are characterised by high genetic homology and comparable brain structures to humans. In addition, behavioural assessments successfully applied in humans could be explored in minipigs to establish similar endpoints in preclinical and clinical studies. Recently, analysis of voice and speech production was established to characterise HD patients. Objective: The aim of this study was to investigate whether vocalisation could also serve as a viable marker for phenotyping minipigs transgenic for Huntington disease (tgHD) and whether tgHD minipigs reveal changes in this domain compared to wildtype (wt) minipigs. Methods: While conducting behavioural testing, vocalisation incidence was documented for a cohort of 14 tgHD and 18 wt minipigs. Statistical analyses were performed using Fisher's Exact Test for group comparisons and McNemar's Test for intra-visit differences between tgHD and wt minipigs. Results: Vocalisation can easily be documented during phenotyping assessments of minipigs. Differences in vocalisation frequency across behavioural conditions were detected between tgHD and wt minipigs. Influence of the genotype on vocalisation was detectable during a period of 1, 5 years. Conclusion: Vocalisation may be a viable marker for phenotyping minipigs transgenic for the Huntington gene. Documentation of vocalisation provides a non-invasive opportunity to capture potential disease signs and explore phenotypic development including the age of disease manifestation. Acknowledgement: This study was funded by the CHDI foundation.